Pengaruh Pengungkapan Identitas Etika Islam Terhadap Kinerja Keuangan Perbankan Syariah Di Indonesia - Nola Marka; Vanica Serly (Universitas Negeri Padang, 2020)
This research aims to examine the influence of Islamic ethical identity disclosure on Sharia banking financial performance in Indonesia. The samples used in this study were Indonesian sharia banks in 2015-2018 with a sampling method of purposive sampling, resulting in a sample of 11 companies. The identity of Islamic ethics is measured using the index of ethical identities and financial performance using Return On Equity, Return On Investment and Financing to Deposit Ratio. The analysis is done using multiple regression models. The results of this study show that: (1) The disclosure of Islamic ethics identities has a positive but insignificant impact on the ROE financial performance with a significance rate of 0.984. (2) Disclosure of Islamic ethics identity has negative and insignificant effect on the financial performance of ROI with significance level 0.065. (3) Disclosure of Islamic ethics identities has a positive and significant impact on the financial performance of FDR with the significance of 0.018.